Kembali Becik’s Traveling Tips on Instagram through Ecolinguistic Lens - Radha Andhra Swari; Made Sani Damayanthi Muliawan; I Made Astu Mahayana (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Studies on ecolinguistics mostly delve into how the media portrays environmental issues in tourism sector, but few to none have examined the way social media promotes sustainable traveling. This study aims to examine Kembali Becik’s traveling tips on Instagram. Designed with descriptive qualitative method, the data were obtained from Kembali Becik’s Instagram account (instagram.com/kembali.becik) in the form of captions and images. Furthermore, data were taken from the posts in six-month period (September 2022-March 2023). Data were analyzed using ecolinguistic theory of salience and visual image analysis. The results showcase certain language patterns in Kembali Becik’s traveling tips, which include constant use of eco-lexicons such as adjectives and nouns. Moreover, the images also strengthen the positive message regarding sustainable practices that can be done while traveling in Bali. Further research needs to be conducted in order to evaluate the portrayal of sustainable traveling in various media.